1995
DOI: 10.1111/j.1432-1033.1995.0962m.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Phosphorylation of Cardiac Troponin-I on Its Interactions with Actin and Cardiac Troponin-C

Abstract: It is known that the phosphorylation of two serine residues on the NH2-terminal extension specific to cardiac troponin-I (Tn-I) modulates the calcium-dependent activation of the myofilaments. The process by which this occurs remains an unsolved puzzle. We have applied a dissective approach to study the effect of this phosphorylation on the interactions between Tn-I and its partner proteins, actin and troponin-C (Tn-C). Using N-[14C]ethylmaleimide-labelled Tn-I in sedimentation assays with F-actin, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 40 publications
6
35
0
Order By: Relevance
“…31p_ NMR spectra showed that only phosphate groups present in the bisphosphorylared species interact with another cTn subunit [6]. Recent studies have shown that bisphosphorylation decreases the affinity of cTnI for cTnC and for actin [28]. However, there exist three further cTnI states, namely the two monophosphorylated ones and the dephosphorylated one as well as multiple cTnT states whose functions are still not known to date.…”
Section: Discussionmentioning
confidence: 98%
“…31p_ NMR spectra showed that only phosphate groups present in the bisphosphorylared species interact with another cTn subunit [6]. Recent studies have shown that bisphosphorylation decreases the affinity of cTnI for cTnC and for actin [28]. However, there exist three further cTnI states, namely the two monophosphorylated ones and the dephosphorylated one as well as multiple cTnT states whose functions are still not known to date.…”
Section: Discussionmentioning
confidence: 98%
“…In the heart, phosphorylation of TnI by PKA occurs following fladrenergic stimulation [17] and may be considered as an adaptive mechanism to prevent overstimulation. The phosphorylation of cardiac TnI has been shown to reduce the affinity of TnC for Ca 2+ [18], thus, promoting more rapid relaxation [9]. Different TnI isoforms from various tissues have been overexpressed in bacterial systems [19,20] and a number of mutants have been produced in order to investigate the structur~func-tion relationship in TnI [7,10,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of these residues causes folding of TnI at its N-terminal extension. 30 This conformational change weakens the cooperative binding of TnI to actin-tropomyosin 31 and reduces the affinity of TnI for TnC, especially in the presence of Ca 2ϩ . 32,33 Because the interaction between TnI and TnC increases Ca 2ϩ binding, reduced TnI/TnC binding lowers the affinity of TnC for Ca 2ϩ .…”
Section: Structural Changes In Tni and Mybp-c After Pka-induced Phospmentioning
confidence: 99%